SYNERGIZING CASH WAQF INTO PROPERTY – THE CASE OF HOUSING INAFFORDABILITY IN ISKANDAR MALAYSIA - Omar, Ismail; Ismail, Nur Azlin (Journal of Technology Management and Business, 2017)
At the early 15th Century, the Ottoman Empire used to incorporate cash waqf into property investment and development. Using the cash waqf as an instrument, they have successfully been able to develop property waqf distinguishably. Similar development has been sighted in the Islamic world years later especially in Egypt, Kuwait and Indonesia. In Malaysia, since the inception of the fatwa on the applicability of cash waqf in 2007, many have been promoting and capitalising the availability of cash waqf into property albeit risky investment. This paper sought to examine the way in which cash waqf is utilised in the growing activities of waqf property. By comparing and contrasting between these two instruments of waqf, one needs to fully understand the importance of inalienability, perpetuity and illiquidity as investment qualities of them. Using secondary data in the case of Iskandar Malaysia, the scenario of inaffordability in owning properties is sighted. Interestingly, therefore, cash waqf offers an alternative in contributing to the success of Transformation Agenda of Affordable Residential Property Waqf in the country. Keywords: Cash waqf - Property waqf – Waqf Property Tranformation Agenda – Iskandar Malaysia